2005
DOI: 10.1111/j.1399-302x.2004.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of a novel high molecular weight, serine‐rich protein (SrpA) with fibril‐mediated adhesion of the oral biofilm bacterium Streptococcus cristatus

Abstract: The surface of the oral plaque bacterium Streptococcus cristatus is decorated with a lateral tuft of fibrils. The fibrillar tuft functions in the adhesion of S. cristatus to heterologous bacterial species in the plaque biofilm. The tuft typically consists of a densely packed fringe of shorter fibrils 238 ± 19 nm long with longer, less abundant fibrils 403 ± 66 nm long projecting through the fringe of short fibrils. The two types of fibrils in the tufts of S. cristatus have been refractory to biochemical separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 27 publications
(61 reference statements)
1
67
0
Order By: Relevance
“…Other streptococcal Srr proteins have been reported to function as adhesins (Wu et al, 1998;Bensing & Sullam, 2002;. Fap1 from Streptococcus parasanguinis (formerly parasanguis) binds to saliva-coated hydroxyapatite (Wu et al, 1998;Wu & Fives-Taylor, 1999), and a Fap1-like protein, SrpA of Streptococcus cristatus, is associated with adhesion to heterologous bacterial species from plaque biofilm (Handley et al, 2005). S. gordonii GspB mediates binding to human platelets (Bensing & Sullam, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other streptococcal Srr proteins have been reported to function as adhesins (Wu et al, 1998;Bensing & Sullam, 2002;. Fap1 from Streptococcus parasanguinis (formerly parasanguis) binds to saliva-coated hydroxyapatite (Wu et al, 1998;Wu & Fives-Taylor, 1999), and a Fap1-like protein, SrpA of Streptococcus cristatus, is associated with adhesion to heterologous bacterial species from plaque biofilm (Handley et al, 2005). S. gordonii GspB mediates binding to human platelets (Bensing & Sullam, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, the CshA polypeptide (259 kDa) produced by S. gordonii has been identified as the structural and functional component of one fibril type (394) ( Table 1). while SrpA has been shown to comprise long (400-nm) fibrils in S. cristatus and to confer coaggregation capabilities (216). Because these fibrillar structures presumably confer a selective advantage to streptococci colonizing the host, perhaps initially by mediating adherence interactions, they are important to consider as potential targets for inhibitors or vaccines.…”
Section: Surface Fibrillar Structuresmentioning
confidence: 99%
“…The sequencing of the large repetitive region was completed by using a transposon mutagenesis strategy which allows us to sequence one 400-600 bp repetitive region at a time and assemble them manually based on the exact transposition insertion sites (Wu & Fives-Taylor, 1999). The unusual repetitive nature of Fap1 was initially thought to be artificial; however, the discovery of Fap1-like proteins in other streptococci, such as Streptococcus gordonii strains M99 and DL1 (Bensing & Sullam, 2002;Takahashi et al, 2002;Vickerman et al, 2007), Streptococcus cristatus (Handley et al, 2005) and the sequenced genome of Streptococcus pneumoniae TIGR4 (Tettelin et al, 2001), has confirmed our findings and stimulated researchers' interest in the area.…”
Section: Identification Of Serine-rich Glycoproteinsmentioning
confidence: 99%
“…sanguinis (Xu et al, 2007) and Strep. cristatus (Handley et al, 2005), and in important human pathogens, including Strep. agalactiae (Glaser et al, 2002), Strep.…”
Section: Identification Of Serine-rich Glycoproteinsmentioning
confidence: 99%